Development and Validation of a Stability Indicating RP-HPLC Method for the Determination of Prucalopride succinate in Bulk and Tablet (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
A very simple, precise, economical, accurate, robust, and reproducible reverse phase-high-performance liquid chromatography method along with stability indicating attributes has been developed for estimating of prucalopride succinate (PRU) in both bulk and tablet formulation (PRUVICT 2). The estimation of the solutes was performed on a Grace C18 column of dimension 150 mm × 4.6 mm, 5 μm. PRU was eluted with acetonitrile: 0.02 M potassium dihydrogen phosphate in the ratio of 20:80 v/v in a 10 min isocratic mode at a flow rate of 1 ml/min at 30°C column temperature and monitored at a wavelength of 277 nm. The retention time of PRU was found to be 5.416 minutes. The Q2b validation of the analytical method revealed good linearity over the concentration range 2–12 μg/mL for IVA with r2 of 0.999. The mean recovery % over the three tested ranges of 50%, 100%, and 150% were found to be 100.173%, 99.077%, and 98.575%, respectively. In intra-day variability study, the % RSDs was detected to be 0.754, 1.032, and 0.482 whereas the inter-day variability study demonstrated % RSDs of 0.797, 0.559, and 0.524, respectively. The acid, alkali, boiled water, hydrogen peroxide, dry heat, and UV radiations based stress studies presented the formation of a variety of characteristic degradation products. The developed analytical method may be employed for the routine analysis of PRU in bulk and tablet formulations.